«Sonata d'Isabel» de Vicent Andrés Estellés: entre dues expressions poètiques - Aparicio, Mariola (Caplletra. Revista Internacional de Filologia, 1997)
The aim of this paper is to offer a contrastive view of the literary style of the Valencian poet Vicent Andrés Estellés. By focusing on one of his latest books published, Sonata d'Isabel, it analyses the different types of diction his poems display, so as to understand and better comprehend the versality of his poetry.